Pengaruh Era Digital terhadap Pelestarian Bahasa Indonesia The Influence of the Digital Era on the Preservation of the Indonesian Language - Aina Mulia Rizky; Devi Syalwa Syahfitri; Innes Ferancia Damanik; Peter Patiangbanua Purba; Tiur Intan Hutauruk; Nurul Azizah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
The digital era has a significant impact on the preservation of the Indonesian language, both in the form of challenges and opportunities. Technological developments facilitate access to information and communication, but also encourage the increased use of slang, abbreviations, and a mixture of foreign languages ​​that can threaten the sustainability of the Indonesian language as a national identity. This study aims to analyze the impact of the digital era on the use of the Indonesian language and formulate strategies to maintain its existence. Using quantitative descriptive methods, data were collected through a survey of 30 respondents. The results of the study show that although the digital era opens up opportunities for strengthening Indonesian language literacy through various digital platforms, challenges such as the degradation of formal language and the increasing use of foreign languages ​​​​are still a threat. Therefore, the active role of the government, educational institutions, and the community is needed to encourage the use of good and correct Indonesian in the digital space. Utilization of technology for the development of digital dictionaries, language learning applications, and language literacy campaigns are the main strategies in preserving the Indonesian language in the digital era.